A chemotaxonomical Study of Four Species Belonging the Genus Arabis L. Cruciferae (Brassicacae) in Iraq - Saeed, Jawhar F.; Bakr , Bnar Kh.; Adham, Aven Nozad (Iraqi Journal of Science, 2022)
This study has been focused on the detection of phenolic compound in aerial parts (stem and leaves)of the species belonging the genus Arabis L. A.Caucasica Willd, A.Sagittata (Bertol)DC, A.Aucheri Boiss, A.nova Vill of family cruciferou (Brassicaceae) which were collected during field trips of the districted of Iraq. Phenolic compounds have been identified by using High Performance Liquid Chromatography (HPLC). Nine standard compounds used for comparison five of them flavonoids ( Rutin, Quercetin, kaempferol, Luteolin and Apigenin) and the other phenolic acid ( Chlorogenic acid, Caffeic acid, Ferulic acid and Rosmarinic acid) , results showed that species vary in containing phenolic compound which can be counted as a taxonomic evidence supporting the taxonomic studied, this researchRosmarinicacid، Kaempferol، Quercetin، Rutin، Apeginin، Chloregenic acid: This compound exist in all species (stem and leaves part) is regarded as a first chemical study of genus Arabis L. in Iraq.